Procedure for Pre-Judicial Settlement of Economic Disputes (Filing A Claim) (Zien Journal of Social Sciences and Humanities, 2023)
This research work is devoted to the analysis of the procedure for pre-trial settlement of economic disputes in the context of filing a claim. The main purpose of the work is to identify the procedural aspects and legal mechanisms that govern the process of filing a claim in economic disputes. The paper analyzes the legislation and judicial practice related to the pre-trial settlement of economic disputes, as well as examines scientific research related to this topic. As a result of the study, the main stages of the process of filing a claim are highlighted, including filing a claim, drafting and filing a claim, as well as the necessary formalities and deadlines that should be observed. Particular attention is paid to the procedure for filing a claim with the court, including the necessary documents that must be submitted to the court, and the requirements for the content of the statement of claim. It also discusses issues related to the determination of the competent court to consider economic disputes and the time frame during which it is necessary to file a claim. At the end of the work, conclusions are drawn about the importance of the correct observance of the procedure for filing a claim in economic disputes, since this is an important stage for ensuring the legality and efficiency of the consideration of disputes in court. Proper observance of the procedure allows you to protect the interests of the parties, ensure fair resolution of disputes and maintain legal stability in the economic sphere.